Greek medicine and the Hippocratic revolution. Critical-historical approach - Ostrowski, Janusz (Journal of Education, Health and Sport, 2022)
Greek civilization contributed a lot to the development of all areas of social life, culture, philosophy and science, including medicine. In the field of medicine, she also drew on the preceding civilizations, mainly Egyptian and Babylonian. Greek medicine, starting from the mythical Asclepius, through the already historical asclepiades, the classical, Hippocratic period with Hippocrates at the forefront, ending with the post-hippocratic period, was a transitional period to subsequent important periods in the development of medicine. The classical period contributed to the reduction of the importance of the supranaturalist factor, which was in force in asplepions in favor of recognizing natural causes considered to be the cause of diseases. Some of the principles presented by the main representative of this period, Hippocrates, especially aphorisms or the medical oath have survived to this day. Other theories underwent natural changes in later periods.